DMBT1 is upregulated in cystic fibrosis, affects ciliary motility, and is reduced by acetylcysteine - Kiefer, Alexander; Plattner, Erika; Ruppel, Renate; Weiss, Christel; Zhou-Suckow, Zhe; Mall, Marcus; Renner, Marcus; Müller, Hanna (Molecular and Cellular Pediatrics, 2022)
Background: Cystic fibrosis (CF) is the most common genetic disorder in the Caucasian population. Despite remarkable improvements in morbidity and mortality during the last decades, the disease still limits survival and reduces quality of life of affected patients. Moreover, CF still represents substantial economic burden for healthcare systems. Inflammation and infection already start in early life and play important roles in pulmonary impairment. The aim of this study is to analyze the potential role of DMBT1, a protein with functions in inflammation, angiogenesis, and epithelial differentiation, in CF. Results: Immunohistochemically DMBT1 protein expression was upregulated in lung tissues of CF patients compared to healthy controls. Additionally, pulmonary expression of Dmbt1 was approximately 6-fold increased in an established transgenic mouse model of CF-like lung disease (ENaC tg) compared to wild-type mice as detected by qRT-PCR. Since acetylcysteine (ACC) has been shown to reduce inflammatory markers in the airways, its potential influence on DMBT1 expression was analyzed. A549 cells stably transfected with an expression plasmid encoding the largest (8kb) DMBT1 variant (DMBT1+ cells) or an empty vector control (DMBT1- cells) and incubated with ACC both showed significantly reduced DMBT1 concentrations in the culture medium (p = 0.0001). To further elucidate the function of DMBT1 in pulmonary airways, respiratory epithelial cells were examined by phase contrast microscopy. Addition of human recombinant DMBT1 resulted in altered cilia motility and irregular beat waves (p < 0.0001) suggesting a potential effect of DMBT1 on airway clearance. Conclusions: DMBT1 is part of inflammatory processes in CF and may be used as a potential biomarker for CF lung disease and a potential tool to monitor CF progression. Furthermore, DMBT1 has a negative effect on ciliary motility thereby possibly compromising airway clearance. Application of ACC, leading to reduced DMBT1 concentrations, could be a potential therapeutic option for CF patients.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Acetylcysteine; Ciliary motility; Cystic fibrosis; DMBT1; Inflammation